The relationship between future self-continuity and intention to use Internet wealth management: The mediating role of tolerance of uncertainty and trait anxiety - Wang, Rongzhao; Lin, Xuanxuan; Ye, Zetong; Gao, Hua; Liu, Jianrong (Frontiers in Psychology, 2022)
This study aimed to analyze the mediating effect of tolerance of uncertainty and trait anxiety on future self-continuity and intention to use Internet wealth management systems. A questionnaire survey was distributed online and a total of 388 participants completed questionnaire, The questionnaire included the following scales: Chinese version of the Future Self-Continuity, Intention to Use the Internet Wealth Management, Tolerance of Uncertainty, and Trait Anxiety. Pearson correlation was used to investigate the correlation coefficient between variables while the sequential regression method was used to analyze relationship between variables. To analyze the collected data, the SPSS 26.0 was used. A two-step procedure was applied to analyze the mediation effect. Confirmatory factor analysis was conducted to test the measurement model. Afterward, the Maximum Likelihood method was used for path analysis, and the Bias-corrected Bootstrap method was used to investigate determine the estimated value and confidence interval of the mediating effect. To analyze the mediation effect, the Mplus 7.0 was used. The results showed that future self-continuity positively predicted individuals’ Internet wealth management systems. Furthermore, tolerance of uncertainty and trait anxiety played complete serial multiple mediating roles between future self-continuity and intention to use Internet wealth management. The role of trait anxiety and tolerance of uncertainty have negative impact on intention to use. This study provides a theoretical basis in personality psychology that Internet financial product suppliers can use to improve the attractiveness of their products. Product managers can subdivide users according to these personality traits to provide customized products.